Development and testing of hybrid precast concrete beam-to-column connections under cyclic loading - Ghayed, H.H.; Razak, H.A.; Sulong, N.H.R. (Elsevier, 2017)
In general, precast concrete structure has insufficient ductility to resist seismic load. Detailed understanding on the behaviour of precast concrete connections are limited and current researches are focused addressing this. In this study, two precast and two monolithic concrete joints for exterior beam-to-column connection were tested under cyclic loading. The installation of precast specimens was prepared using dry type method while the monolithic joints were casted in-situ. The evaluation of seismic performance of the joints was conducted by applying hysteretic reverse cyclic loading until failure. Information regarding the strength, ductility and stiffness properties of the connection were recorded and analysed. Based on the test results and damage condition, the initial design of the joint was improved. Consequently, a new joint was constructed and tested, which exhibited a better performance. Precast concrete connections showed stable load–displacement cycles and dissipated a higher energy. The structural drift obtained was up to 9.0%. Pinching and deterioration were attained at a drift ratio of 4.5%. Also, there was improvement in the tested precast joints based on deflection, plastic hinges, crack pattern and shear deformation. Thus, the precast joints had a satisfactory resistance to seismic loads.